2021
DOI: 10.1159/000511746
|View full text |Cite
|
Sign up to set email alerts
|

Application of Percutaneous Holmium Laser Lithotripsy in the Treatment of Bladder Calculi with Lower Urinary Tract Obstruction or Pelvic Joint Disease

Abstract: <b><i>Objective:</i></b> The aim was to summarize the experience of percutaneous holmium laser lithotripsy in the treatment of bladder calculi with lower urinary tract obstruction or pelvic joint disease in our hospital, explore its efficacy and safety, and improve the minimally invasive surgical technique for bladder calculi. <b><i>Methods:</i></b> The clinical data of 61 patients with bladder calculi combined with lower urinary tract obstructive diseases, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…It is concluded that percutaneous holmium laser lithotripsy is an improved minimally invasive surgical technique for the treatment of bladder stones. It has the advantages of clear surgical field, high stone retrieval efficiency, small trauma, low pressure of bladder perfusion, auxiliary injury, and low incidence of infection [ 6 ]. Sun compares the different effects of two-shift and single-shift flexible ureteroscope holmium laser lithotripsy for the treatment of kidney stones larger than 1.5 cm on surgical results and operator comfort.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that percutaneous holmium laser lithotripsy is an improved minimally invasive surgical technique for the treatment of bladder stones. It has the advantages of clear surgical field, high stone retrieval efficiency, small trauma, low pressure of bladder perfusion, auxiliary injury, and low incidence of infection [ 6 ]. Sun compares the different effects of two-shift and single-shift flexible ureteroscope holmium laser lithotripsy for the treatment of kidney stones larger than 1.5 cm on surgical results and operator comfort.…”
Section: Introductionmentioning
confidence: 99%